2020
DOI: 10.1186/s12888-020-02877-6
|View full text |Cite
|
Sign up to set email alerts
|

Distinct effects of over-general autobiographical memory on suicidal ideation among depressed and healthy people

Abstract: Background Childhood trauma and over-general autobiographical memory (OGM) are crucial risk factors of suicide. This study aimed to investigate whether suicidal ideation was predicted by one’s childhood trauma and OGM and the mechanism of OGM underlying suicidal ideation in depression patients and healthy controls. Methods A total of 180 depression patients and 176 matched healthy individuals were recruited in this study. Data were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The outdoor group's specific AM was significantly higher and its overgeneral AM was significantly lower than the indoor group's for sessions three and four. Theoretically biased thoughts, including memories and ruminations, influence processing of incoming information and play a primary role in the development and maintenance of depression [13], and depression is empirically associated with rumination [20,21] and specific/overgeneral AM [17][18][19]. Therefore, exposure to nature for four 45 min sessions successfully reduces rumination and results in a desirable impact on AM, as found in the present study, and should be regarded as favorable for decreasing depression.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The outdoor group's specific AM was significantly higher and its overgeneral AM was significantly lower than the indoor group's for sessions three and four. Theoretically biased thoughts, including memories and ruminations, influence processing of incoming information and play a primary role in the development and maintenance of depression [13], and depression is empirically associated with rumination [20,21] and specific/overgeneral AM [17][18][19]. Therefore, exposure to nature for four 45 min sessions successfully reduces rumination and results in a desirable impact on AM, as found in the present study, and should be regarded as favorable for decreasing depression.…”
Section: Discussionsupporting
confidence: 65%
“…While biased memory is related to biased attention and processing, there is a difference in autobiographical memory recall (i.e., less specific but excessive generalization in memory) between depressed and non-depressed patients. Ample empirical evidence explains the relationships between depression and biased attention [14][15][16], biased memory [17][18][19], and ruminative thoughts [20,21], and through intervention, these biases can be modified [22][23][24][25].…”
Section: Identify Evidence-based Outcome Measurementsmentioning
confidence: 99%
“…64), a range of 3–9. Overall, 6 (12.5%) studies were rated as ‘poor’ (NOS score = 3–4), 10 (20.8%) studies were rated as ‘fair’ (NOS score = 5), 11 (22.9%) studies were rated as ‘good’ (NOS score = 6), and 21 (43.8.%) studies received a rating considered as ‘high’ (NOS score > 6) ( Huntjens et al, 2014 ; Neshat Doost et al, 2014 ; Harris et al, 2016 ; Parlar et al, 2016 ; Wang et al, 2016 ; Wittekind et al, 2016 ; Peltonen et al, 2017 ; Saleh et al, 2017 ; Wittekind et al, 2017 ; Feurer et al, 2018 ; Kaczmarczyk et al, 2018 ; Tian et al, 2018 ; Viard et al, 2019 ; Jiang et al, 2020 ; Barry et al, 2021 ; Bendstrup et al, 2021 ; Chiasson et al, 2022 ; D’Amico et al, 2022 ; Pacheco and Scheeringa, 2022 ; Thomson and Jaque, 2022 ; Fishere and Habermas, 2023 ). The representativeness of samples was mixed (clinical and healthy samples), including children, adolescents, and adults, and most of the included studies did not report either on non-response or a priori power analyses or otherwise justified their sample sizes.…”
Section: Resultsmentioning
confidence: 99%
“…The representativeness of samples was mixed (clinical and healthy samples), including children, adolescents, and adults, and most of the included studies did not report either on non-response or a priori power analyses or otherwise justified their sample sizes. More than half of the included studies ( N = 29) controlled for covariates in their design or analysis (i.e., age, gender) and 19 studies used a control group for childhood trauma ( Huntjens et al, 2014 ; Neshat Doost et al, 2014 ; Berthelot et al, 2015 ; Harris et al, 2016 ; Parlar et al, 2016 ; Wang et al, 2016 ; Wittekind et al, 2016 ; McCrory et al, 2017 ; Saleh et al, 2017 ; Wittekind et al, 2017 ; Kaczmarczyk et al, 2018 ; Tian et al, 2018 ; Viard et al, 2019 ; Jiang et al, 2020 ; Barry et al, 2021 ; Bendstrup et al, 2021 ; Chiasson et al, 2022 ; Pacheco and Scheeringa, 2022 ; Fishere and Habermas, 2023 ) (see Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies that have not excluded these individuals have not reported lifetime suicide attempts or suicidal ideation among healthy volunteers, leaving the data out of tables and text and sometimes denoting data for these variables as not applicable . However, lifetime suicide attempts and suicidal ideation, which do not necessarily occur in the same populations, have been reported in healthy volunteers, albeit in small samples recruited for biological or clinical studies of various psychiatric disorders, and larger epidemiologic or registry samples provide supporting evidence . If lifetime suicide attempts in healthy volunteers are common, this could have implications for suicide risk screening and nosology.…”
Section: Introductionmentioning
confidence: 99%